Analisis Putusan Mahkamah Konstitusi Terkait Dengan Penetapan Tersangka Sebagai Objek Praperadilan (Studi Putusan Nomor 73/Pid.Pra/2018/Pn.Mdn) - Josep Panggabean (Iuris Studia: Jurnal Kajian Hukum, 2020)
A person's freedom can be limited for the sake of law enforcement, as stated in article 50 of the Criminal Code which states that: "Whoever commits an act to implement the provisions of the law is not punished." In connection with the activities of investigators that can carry out arrests and even detention, the criminal procedure law, through its provisions, forces the elimination of the universally recognized principle of freedom of a person. This research is a normative legal research with the research method is library research. Based on the research results it is known that the Constitutional Court Decision No. 21 / PUU-XII / 2014, has made new regulations by expanding pretrial powers, which include testing the legality of the determination of the suspect, searches and confiscation, Constitutional Court decision No. 21 / PUU-XII / 2014, has the implication of prioritizing aspects of human rights and legal certainty for someone who is named a suspect, giving the suspect broad rights to defend himself from possible errors in the legal process during the investigation stage, the basis for the consideration of the pretrial judge to grant the petitioner part of it in the case No. 73 / Pid.Pra / 2018 / Pn.Mdn., Is because the determination of the suspect is carried out earlier than the suspect's investigation order, so that the determination of the suspect becomes invalid due to defective procedures